Mechanical thrombectomy using the new solitaire™ platinum stent-retriever - Pfaff, Johannes; Rohde, Stefan; Engelhorn, Tobias; Dörfler, Arnd; Bendszus, Martin; Möhlenbruch, Markus Alfred (Clinical neuroradiology, 2018)
The application of radiopaque markers to the Solitaire™ stent-retriever for better visibility during mechanical thrombectomy (MT) has the potential to alter the well-known characteristics of the device; however, it is uncertain whether this adjustment influences efficacy or safety of the enhanced stent-retriever.
Published online: 10 January 2018
Gesehen am 18.02.2020